FREQUENCY AND THE RELATED SOCIO-DEMOGRAPHIC AND CLINICAL FACTORS OF PHANTOM LIMB PAIN IN TRAUMATIC AMPUTEES PRESENTING AT A TERTIARY CARE REHABILITATION SETUP: Phantom Limb Pain in Traumatic Amputees - Ayaz, Saeed Bin; Ikram, Muhammad; Matee, Sumeera; Fahim, Muhammad; Khan, Atif Ahmed; Ahmad, Mahmood (Pakistan Armed Forces Medical Journal, 2015)
Objective: To find out the frequency of phantom limb pain (PLP) in a sample of Pakistani amputee population presenting with amputation due to trauma and to investigate its relationship with different socio-demographic and clinical factors. Study Design: A cross-sectional descriptive study. Place and Duration of Study: Armed Forces Institute of Rehabilitation Medicine, Rawalpindi from August 2010 to October 2013. Material and Methods: Through non-probability purposive sampling, patients of both genders and all ages having a traumatic etiology of amputation were sampled from the outdoor amputee clinic and the indoor amputee ward. Patients having diabetes mellitus, polyneuropathy, memory loss, cognitive deficits and established history of psychiatric disorders were excluded. Through face to face semi structured interviews, information was obtained about presence of PLP, gender, location (urban or rural), ethnicity based on Pakistani provinces (Punjab, Sindh, Khyber Pakhtunkhwa, Balochistan, Azad Jammu and Kashmir), monthly income in Pakistani Rupees (PKR) (<10,000, 10,000 – <50,000 and >50,000), level of education (grade <5 , grade 5 – 10, and grade >10), level of amputation and cause of trauma (fall from height, motor vehicle accident, blast injury, bullet injury or others). Results: Out of 268 patients (mean age 28 ± 6 years), 266 (99.3%) were male and 2 (0.7%) were female. Majority (79.1%) were rural based, Punjabis (44.8%), had a monthly income <10,000 PKR (85.4%), education from grade 5 – 10 (80.2%) and a lower limb amputation (86.9%). The commonest cause was blast injuries (72.8%). PLP was present in 42.5% (n=114) of the individuals and it was not significantly related to gender, living location, ethnicity based on Pakistani provinces, level of education, monthly income, cause of traumatic amputation and level of amputation. Conclusion: PLP was found in 42.5% of our sample of Pakistani traumatic amputees. The frequency was not related to gender, monthly income, ethnicity based on provinces, education, rural or urban based living and etiology or level of amputation.